Disponibilidade da água em afloramentos rochosos no semiárido: qualidades, usos e potencialidades - Pereira, Hevelyne Figueirêdo (2019)
The semi-arid region is characterized by climate variability and water scarcity, where the slow and quiet action of the dry period causes negative impacts that result in severe social, economic and environmental damage. The main objective of this work was to evaluate the quality of the water found in rocky outcrops in the rural area of the municipality of Cabaceiras (PB) and to report their use conditions according to the existing legislation, verifying the possibilities of use of the waters analyzed according to the results. Three tanks found in the slab in the community of San Francisco in the mediations of the village known as Curatá de Dentro were studied. The methodological procedure approached was used by the inductive method of a quantitative-qualitative nature. Initially, they consisted of bibliographic survey, field research, laboratory analysis and cabinet work. The results showed that the waters of reservoirs P01 and P02 are unsuitable for domestic consumption according to the bacteriological and physicochemical parameters found, however they can be used for other purposes according to Conama Resolution Nº. 357 (BRAZIL, 2005). P03 was identified in a process of eutrophication, classifying the reservoir as unsuitable for various uses due to the toxic probability of its waters. It is pointed out that the analysis performed in this study about the possibilities of water use in the studied tanks, part of the premise of the use of raw water. It was concluded that the waters of the reservoirs could be used for other uses if they were intended for a primary treatment process.